'Made with love, filled with hope'. Knitted Knockers and the materiality of care: Their impact on the women who make and receive them. (1st March 2020) - MacDonald, Juliette; Peach, Andrea
This reflective case study sets out to ask 'How do participatory textile-making projects engage and impact participants and recipients?' by focusing on Knitted Knockers UK, a global network of knitters who voluntarily create prosthetics for women following mastectomy or lumpectomy. The article examines the choices women are faced with following breast cancer surgery, and considers 'softer options' to surgical reconstruction, including knitted prosthetics. Drawing on qualitative data gathered via personal communications and social media, personal experience of breast cancer diagnosis and treatment, and feminist discourse with relation to breast cancer and the body, the authors evaluate the relationship between well-being, healthcare and digitally connected knitting communities. They offer reflections on the materiality of care the Knitted Knockers represent and consider the role these hand-knitted prosthetics can play in providing a sense of community and emotional well-being for both the creators and the recipients of these knitted gifts.